2006
DOI: 10.1073/pnas.0511045103
|View full text |Cite
|
Sign up to set email alerts
|

Cell-type-specific signatures of microRNAs on target mRNA expression

Abstract: Although it is known that the human genome contains hundreds of microRNA (miRNA) genes and that each miRNA can regulate a large number of mRNA targets, the overall effect of miRNAs on mRNA tissue profiles has not been systematically elucidated. Here, we show that predicted human mRNA targets of several highly tissue-specific miRNAs are typically expressed in the same tissue as the miRNA but at significantly lower levels than in tissues where the miRNA is not present. Conversely, highly expressed genes are ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
515
4
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 603 publications
(557 citation statements)
references
References 27 publications
30
515
4
8
Order By: Relevance
“…and tissues (Sood et al, 2006); thus, miRNAs could be acting to prevent transdifferentiation by preventing translation of potentially leaky master switch genes-in other words, have a protective role. This is supported by studies of pancreas regeneration in mammals, where Neurogenin 3 is silenced by miRNA after partial pancreatectomy (Joglekar et al, 2007).…”
Section: Micrornasmentioning
confidence: 99%
“…and tissues (Sood et al, 2006); thus, miRNAs could be acting to prevent transdifferentiation by preventing translation of potentially leaky master switch genes-in other words, have a protective role. This is supported by studies of pancreas regeneration in mammals, where Neurogenin 3 is silenced by miRNA after partial pancreatectomy (Joglekar et al, 2007).…”
Section: Micrornasmentioning
confidence: 99%
“…There are a few hundred experimentally sequenced and predicted human miRNAs [10][11][12][13], and together, they hold the potential to regulate thousands of genes impacting a large variety of biological processes. Expression of many miRNAs is regulated in a tissue-specific and temporal manner, the full biological relevance of which remains to be unraveled [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…miRs guide the pairing of miRISC, with imperfect complementarity, to sequences in target mRNAs, thus resulting in their subsequent destabilization and translational repression of the target 3 . The 'seed sequence' , at nucleotides 2-8, is a key determinant for miRISC-target recognition 4,5 . Recent data have shown that 35-40% of miR-binding sites are found in 3′ untranslated regions (UTRs), 40-50% in coding regions and <5% in 5′-UTR regions of mRNAs 6,7 .…”
mentioning
confidence: 99%